Proton capture reactions in medium-heavy nuclei relevant to p-process nucleosynthesis - Foteinou, V.; Axiotis, M.; Lagoyannis, A.; Demetriou, P.; Becker, H.-W.; Rogalla, D.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2019)
Cross-section measurements of proton-capture reactions on Molybdenum isotopes have been performed at beam energies from 2.0 to 6.2 MeV. The cross-section data obtained in this work are compared with those predicted by theory. The latter were calculated using the latest version of the TALYS Hauser-Feshbach (HF) theory code [1] (version 1.6). In these calculations, various phenomenological and (semi)microscopic models were used for the nucleon-nucleus and the α-particle-nucleus optical model potential, the nuclear level densities and the γ-ray strength function.